2018
DOI: 10.3390/ma11071093
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure-Mechanical Properties of Hybrid Fibres-Reinforced Self-Compacting Lightweight Concrete with Perlite Aggregate

Abstract: The purpose of this paper is to determine the influence of the lightweight porous perlite aggregate and two widely used types of fibres on the physical and mechanical properties, frost durability and microstructure of self-compacting lightweight concrete (SCLC). The experimental investigation consisted of tests carried out on cubes and prismatic samples made of SCLC and fibres-reinforced SCLC with variable content ranging from 0.5 to 1% of basalt fibres (BF) and/or 0.5% of steel fibres (SF). In this study, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…The relationship between those two parameters can be described by the polynomial second-order model, with the determination coefficient being equal to 0.866. The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers. The authors of [64] showed that lower fiber-reinforced concrete strength should be combined with a two-fold increase in air content in this The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers.…”
Section: Discussion On the Physical And Mechanical Properties Of The supporting
confidence: 68%
See 2 more Smart Citations
“…The relationship between those two parameters can be described by the polynomial second-order model, with the determination coefficient being equal to 0.866. The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers. The authors of [64] showed that lower fiber-reinforced concrete strength should be combined with a two-fold increase in air content in this The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers.…”
Section: Discussion On the Physical And Mechanical Properties Of The supporting
confidence: 68%
“…The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers. The authors of [64] showed that lower fiber-reinforced concrete strength should be combined with a two-fold increase in air content in this The results for water absorptivity indicate the increased porosity of the mixtures due to the application of fibers, especially steel ones, which was demonstrated by other researchers [64] in studies on concretes supplemented with steel and basalt fibers. The authors of [64] showed that lower fiber-reinforced concrete strength should be combined with a two-fold increase in air content in this mix, as well as higher open porosity in the hardened concretes.…”
Section: Discussion On the Physical And Mechanical Properties Of The supporting
confidence: 68%
See 1 more Smart Citation
“…Table 6 presents the results of the durability and physical properties of mortars. Numerous studies confirming the influence of expanded perlite on the physical properties of cement composites are known in the literature [63][64][65][66] Analyzing the results, it can be unequivocally stated that the replacement of natural aggregate with expanded perlite reduces the density of mortars, which decreases as the number of perlite increases. This is due to the low specific gravity of perlite and high porosity of aggregate, which contributes to increasing the porosity of ready-mixed mortars.…”
Section: Methodsmentioning
confidence: 92%
“…Widespread use of nano-modified and mineral additives are in the various concretes compositions [7][8][9]. There is an active research of the modifying additives effect on shrinkable deformations of the foam concrete mix [10], as well as on density in normal moisture content conditions, on compressive strength and tensile strength during bending of cement composites [11][12][13], is being conducted.…”
Section: Introductionmentioning
confidence: 99%